Whole genomic analysis of human G8P[14] group A rotavirus detected from community gastroenteritis outbreak. Issue 8 (8th May 2018) - Mori, Kohji; Nakazawa, Haruyuki; Hase, Shinichi; Nagano, Miyuki; Kimoto, Kana; Oda, Mayuko; Somura, Yoshiko; Akiba, Tetsuya; Hayashi, Yukinao; Shinkai, Takayuki; Sadamasu, Kenji
Abstract : Several suspected cases of zoonotic transmission of group A rotavirus (RVA)‐related gastroenteritis were reported previously. In August 2012, G8P[14] RVA was detected in fecal specimens from a community gastroenteritis outbreak occurring during a school trip. In this study, additional analyses were performed and it was found that this strain had the G8‐P[14]‐I2‐R2‐C2‐M2‐A3‐N2‐T6‐E2‐H3 sequence, similar to bovine‐like RVA strains. Some contamination by emesis and diarrheic feces was observed near a rest room in the lodging area. Contact history with animals was unknown in members of this school trip, and this case implied that the strain may have acquired the ability for person‐to‐person transmission.